Manganese-Catalyzed C(sp2)–H Addition to Polar Unsaturated Bonds - Liu, Ting; Wang, Congyang (Synlett, 2021)
Transition-metal-catalyzed nucleophilic C–H addition of hydrocarbons to polar unsaturated bonds could intrinsically avoid prefunctionalization of substrates and formation of waste byproducts, thus featuring high step- and atom-economy. As the third most abundant transition metal, manganese-catalyzed C–H addition to polar unsaturated bonds remains challenging, partially due to the difficulty in building a closed catalytic cycle of manganese. In the past few years, we have developed manganese catalysis to enable the sp2-hydrid C–H addition to polar unsaturated bonds (e.g., imines, aldehydes, nitriles), which will be discussed in this personal account.1 Introduction2 Mn-Catalyzed N-Directed C(sp2)–H Addition to Polar Unsaturated Bonds3 Mn-Catalyzed O-Directed C(sp2)–H Addition to Polar Unsaturated Bonds4 Conclusion
Keywords: manganese; catalysis; C–H activation; polar unsaturated bonds; organic synthesis